Fit of a Rayleigh Distribution on Censored Data — Study of Atrial Fibrillation - Rey, W. J. J.; Martin, L. J.; Bernard, R. (Methods of Information in Medicine, 1976)
This paper attempts to verify whether the threat to life caused by the fact that an event is delayed increases with the length of the delay. Such a mechanism would be a safety feature. Assessment is given in the special case of the RRj variate or interval between successive cardiac contractions for patients in atrial fibrillation. Fit of a Rayleigh distribution on censored data and Monte Carlo methodology assessment are discussed. In terms of reliability theory, we present a linearly increasing failure rate model and test whether the observed process permits its validation.
Keywords: Statistical Estimation; Hazard Rate; Biological Mechanism; Atrial Fibrillation